Peran Mata Kuliah Hizbul Wathan Dalam Membentuk Karakter Tanggung Jawab Mahasiswa. - Lestari, Mas Roro Diah Wahyu; Irmawati, Sri; Sania, Sania (Universitas Negeri Makassar, 2024)
This research was motivated by the interest of Hizbul Wathan Course Lecturers about the character of students' responsibilities towards the tasks given by lecturers. An attitude of responsibility to oneself has the advantage of attitudes such as honest, disciplined, and trustworthy. The purpose of this study was to determine the influence of the relationship between Hizbul Wathan courses and to find out how much the relationship between Hizbul Wathan subjects and the character of responsibility among students. Samples used in PGSD UMJ semester 5 students. The method used in this study is quantitative discriptive with Pearson correlation statistical data processing. Data analysis through written tests. The results of the study were the relationship between Hizbul Wathan courses and the character of responsibility. The teaching of Hizbul Wathan (HW) courses and the character of responsibility have a strong relationship of 0.764 during one semester. This research is useful to related parties, namely Hizbul Wathan course lecturers, students, faculties, and Hizbul Wathan Qobilah Universitas Muhammadiyah Jakarta.